Effects of chromium supplementation on physiology, feed intake, and insulin related metabolism in growing pigs subjected to heat stress. Issue 1 (1st February 2017) - Liu, F.; Cottrell, J. J.; Wijesiriwardana, U.; Kelly, F. W.; Chauhan, S. S.; Pustovit, R. V.; Gonzales-Rivas, P. A.; DiGiacomo, K.; Leury, B. J.; Celi, P.; Dunshea, F. R.
Abstract: Improving insulin sensitivity may reduce impacts of heat stress (HS) in pigs by facilitating heat dissipation. Chromium (Cr) has been reported to improve insulin sensitivity in pigs. Therefore, the aim of this experiment was to investigate whether Cr supplementation can mitigate HS in growing pigs. Thirty-six gilts were randomly assigned to 2 diets containing 0 (control) or 400 ppb Cr. After 14 d the supplemented pigs were allocated to either 8 d thermoneutral (20°C constant; TN) or cyclic HS (35°C, 0900 h to 1700 h) conditions and continued their respective diet ( n = 9 per group). Growth performance was recorded during the 14-d supplementation period. The physiological responses to HS were monitored by measuring respiration rate, rectal temperature, blood gas chemistry, and feed intake during thermal exposure. Kinetics of plasma glucose, insulin and NEFA were studied by intravenous glucose tolerance test (IVGTT) on d 8 of thermal treatment. Results showed Cr alleviated the HS-increased rectal temperature ( P < 0.05) and respiration rate ( P < 0.01) at 1300 h and 1600 h during thermal exposure. However, Cr did not mitigate the reduction in average daily feed intake which was reduced by 35% during HS or the HS-induced respiratory alkalosis. Chromium tended to increase average daily gain (0.86 vs. 0.95 kg, P = 0.070) during the 14-d supplementation under TN conditions before thermal exposure, which might be associated with the potential of Cr in improving overall insulin sensitivity, as evidenced by a reduced insulin resistance index calculated by Homeostatic Model Assessment (HOMA-IR; 0.65 vs. 0.51, P = 0.013) and a tendency of reduced fasting plasma insulin concentration (1.97 vs. 1.67 μU/mL, P = 0.094). Heat stress decreased the acute insulin releasing rate ( P = 0.012) and consequently slowed glucose clearance rate ( P = 0.035) during IVGTT. Besides, HS enlarged the values of area under the curve of NEFA during IVGTT ( P < 0.01), indicating a reduced lipid mobilization. In conclusion, HS reduced insulin response to IVGTT. Chromium supplementation exhibited a potential in improving insulin sensitivity and mitigating HS symptoms in growing pigs.